2022
DOI: 10.3390/jmse10070968
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Remotely Sensed Sediment Grain Size Evolution Characteristics along the Southwest Coast of Laizhou Bay Based on Support Vector Machine Learning

Abstract: Grain size is the basic property of intertidal zone sediment. Grain size acts as an indicator of sedimentary processes and geomorphological evolution under human and nature interactions. The remote sensing technique provides an alternative for sediment grain-size parameter monitoring with the advantages of wide coverage and real-time surveying. This paper attempted to map the distributions of three sediment grain size contents and the mean grain size with multitemporal Landsat images along the southwestern coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Additionally, due to the dynamic nature of coastal regions, it may be necessary to carry out frequent surveys, which further increases the associated time and costs. For this reason, in recent years, there has been increased interest in developing the use of remote sensing techniques to monitor coastal environments (e.g., [1,4,5]). Considering that more than 99% of beaches are not monitored, the use of remote sensing could offer significant promise in supporting the monitoring and protection of coastal areas and local communities from the ever increasing threat of sea level rise and changes due to climate change [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, due to the dynamic nature of coastal regions, it may be necessary to carry out frequent surveys, which further increases the associated time and costs. For this reason, in recent years, there has been increased interest in developing the use of remote sensing techniques to monitor coastal environments (e.g., [1,4,5]). Considering that more than 99% of beaches are not monitored, the use of remote sensing could offer significant promise in supporting the monitoring and protection of coastal areas and local communities from the ever increasing threat of sea level rise and changes due to climate change [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have used remote sensing techniques to characterise sediment grain size and their properties in inter-tidal areas largely focused on using data derived from the visible range of the electromagnetic spectrum (e.g., [4,[7][8][9]). For example, Yu et al [4] initially found low correlations between the reflectance from multi-temporal Landsat data and grain size, but incorporated the use of a support vector machine (SVM) to find a coarsening trend in grain size, which agreed with the field measurements. However, a major limitation of optical satellite approaches is the requirement for near cloud-free conditions, which can be problematic for monitoring a large proportion of coastal areas across the world.…”
Section: Introductionmentioning
confidence: 99%